Handbook of research on e-services in the public sector : e-government strategies and advancements - Al Ajeeli, Abid; Al-Bastaki, Yousif A. Latif (Hershey PA : Information Science Reference, 2010)
"This book assists its readers in recommending formulation of ICT strategies for e-government implementation and maintenance from the perspective of acknowledging the importance of e-Governance for building institutions to achieve transparency and accountability, and eventually democratic governance"--Provided by publisher.